Sosialisasi Pentingnya Penggunaan Pembenah Tanah Orgnaik Pada Tanaman Kelapa Sawit Di Kelompok Tani Bangun Bersama - Ismoyojati, Roni (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
Organic soil conditioners are important to be given to the land to maintain good soil quality. In oil palm cultivation, many farmers still only apply fertilization using inorganic fertilizers without being balanced with the use of organic materials. The purpose of this community service is to provide insight into the importance of using organic soil conditioners in oil palm cultivation and as an effective means of communication between academics and the community directly in disseminating knowledge and technology. The community service method is carried out in three stages, namely: 1). Preparation stage by preparing the necessary tools and coordinating with the local village government and the Bangun Bersama farmer group; 2) The implementation stage of the activity is carried out with lectures and discussions; 3) Evaluation stage by providing feedback in the form of filling out a questionnaire form by participants. The results of this community service can be said to have gone well and participants asked that in the coming years this kind of community service activity be carried out in the Bangun Bersama farmer group. Community service participants felt an extraordinary impact with the increase in knowledge about organic soil conditioners, thereby increasing literacy for farmers.